Analysis of Implementation of the Bedside SBAR Handover Method with Patient Satisfaction - Harmaniati, Harmaniati; Ibnu, Faizal; Ratnaningsih, Tri (Indonesian Journal of Global Health Research, 2024)
The implementation of bedside handover can make patients actively involved in handover activities, so that there is effective communication practice by nurses to patients. The development of bedside handover is considered to increase patient satisfaction. Objective: Based on this phenomenon, this research was conducted to find out whether the implementation of bedside handover is related to patient satisfaction at the Graha Amerta Installation at RSUD dr. Soetomo. This research uses a quantitative research design with a correlation research design and a cross-sectional approach. This research was conducted at 4th and 5th Floor of Graha Amerta RSUD Dr. Soetomo Surabaya in January – April 2024 with a sample of 40 patients determined through consecutive sampling. Based on the research results, the Spearman Rho statistical test results obtained a value of p = 0.022 or p < 0.05, which means there is a relationship between the implementation of the SBAR bedside handover method and nurse satisfaction at Graha Amerta Dr Soetomo Hospital Surabaya. The results of the Spearman Rho statistical test obtained a correlation coefficient value of 0.361. The higher the level of implementation of the SBAR bedside handover method, the higher the patient satisfaction at Graha Amerta RSUD Dr Soetomo Surabaya.